2007
DOI: 10.1152/ajpregu.00781.2006
|View full text |Cite
|
Sign up to set email alerts
|

The farnesoid X receptor FXRα/NR1H4 acquired ligand specificity for bile salts late in vertebrate evolution

Abstract: There is an extra sequence in the middle of the sFxr ligand binding domain (LBD) compared with the LBD of FXR␣. Luciferase reporter assays demonstrated that sFxr responds weakly to scymnol sulfate, bile salts, and synthetic FXR␣ ligands, in striking difference from human FXR␣ (hFXR␣). Interestingly, all-trans retinoic acid was capable of transactivating both hFXR␣ and sFxr. When the extra amino acids in the sFxr LBD were deleted and replaced with the corresponding sequence from hFXR␣, the mutant sFxr gained re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…44,45 XN has been shown to be a natural ligand for FXR. 37 However, we found that XN inhibits TNF-induced NF-B activation in both FXR-positive and -negative cell lines, suggesting that FXR is not required for the NF-B-inhibitory activity of XN. However, this chalcone also inhibited bile acid-induced NF-B activation, which is linked with FXR.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…44,45 XN has been shown to be a natural ligand for FXR. 37 However, we found that XN inhibits TNF-induced NF-B activation in both FXR-positive and -negative cell lines, suggesting that FXR is not required for the NF-B-inhibitory activity of XN. However, this chalcone also inhibited bile acid-induced NF-B activation, which is linked with FXR.…”
Section: Discussionmentioning
confidence: 67%
“…37 We found that bile acids can activate NF-B in MCF-7 cells and that XN can suppress NF-B activation ( Figure 7D). Like XN, we found that guggulsterone also suppressed bile acid-induced NF-B activation.…”
Section: Inhibition Of the Nf-b-signaling Cascade By Xn Is Independenmentioning
confidence: 75%
“…However, as a permissive nuclear receptor, FXR can also be activated through the ligand of its obligated heterodimeric partner, the retinoid X receptor (RXR, NR2B) ( 29,30 ), where 9-cis retinoic acid (9cRA) is its specifi c ligand ( 31 ( 32 ). While characterizing a primitive Fxr from the marine skate Leucoraja erinacea, we have also observed that atRA is a conserved activator of FXR in a reporter assay using cotransfection of skate Fxr and human RXR ␣ expression constructs ( 33 ). These observations raise two questions: (1) Is atRA or its metabolite a true ligand for FXR?…”
Section: Sirna Oligonucleotidesmentioning
confidence: 86%
“…Human FXR ( hFXR ), RXR ␣ (hRXR ␣ ) and I-BABP promoter reporter constructs are described in a previous article ( 33 ). Mouse HNF4 ␣ and PGC-1 ␣ expression plasmids were provided by Dr. Peter Edwards (University of California at Los Angeles, Los Angeles, CA).…”
Section: Plasmid Constructsmentioning
confidence: 99%
See 1 more Smart Citation